Effect of exercise on therapeutic response in depression treatment - Tasci, Gulay; Baykara, Sema; Gurok, M. Gurkan; Atmaca, Murad (Taylor & Francis Ltd, 2019)
OBJECTIVES: The aim of this study is to investigate the effect of exercise on therapeutic response in depression treatment. METHODS: Thirty-three patients admitted to the Psychiatry Department of Firat University Hospital and diagnosed with major depressive disorder according to DSM-IV criteria and met the study criteria were included in the study. The patients in Group 1 were treated with antidepressant medication and were asked for brisk walking for at least 30 minutes a day, at least 4 days a week, for 12 weeks. Only antidepressant medication was given to the patients in Group 2. The Hamilton Depression Rating Scale, the Hamilton Anxiety Rating Scale, and the Clinical Global Impression Scale were applied to both groups at baseline and at the end of 6 weeks and 12 weeks. RESULTS: Anxiety and depression levels decreased in both groups. The decrease in anxiety and depression scores with antidepressant use is an expected outcome. However, there was a statistically more decrease in the average-scaled scores in the Group treated with antidepressant and exercise than the Group treated with only antidepressant. CONCLUSIONS: Exercise had a positive effect on the therapeutic response in depression treatment. However, long-term studies in larger sample groups are needed.
Keywords: Depression; exercise; therapeutic response